Eye care interventions that reduce access inequities for women, rural residents and older people in low-middle-income countries: a scoping review - Cardona, Magnolia; Alwenya, Kennedy; Rehman, Atiq ur; Olalo, Sarah; Thai, An; Rangi, Mediya; Perez, Yadira; Lee, Ling (Frontiers in Public Health, 2025)
IntroductionWomen, older people and rural residents in low-middle-income settings are mainly impacted by the economic and psychosocial consequences of preventable blindness from undiagnosed and untreated cataracts diabetic retinopathy.MethodsThis review of PubMed 2002-2023 and the grey literature aimed to identify strategies effective in reducing access inequities to eye health screening and treatment for the above vulnerable groups.ResultsThirty-nine publications from 16 countries were included. Fifteen focused on cataract, 17 on diabetic retinopathy, and seven on general ophthalmology. This article focuses on the twenty-four studies of moderate or high quality. Rural residents were more likely to benefit (16 studies) while direct effectiveness among women were reported in seven studies. Only three studies reported actual benefits for older people. Outreach services and teleophthalmology were effective interventions increasing screening attendance and referral rates for women and rural residents. Health financing to enhance cataract surgery acceptance and actual surgical rates reported effectiveness for rural residents but showed only modest improvements. Digital technology improved overall appointment uptake and referral adherence for rural residents but not significantly for women. Teleophthalmology was successful in building local capacity for accurate diagnosis but its impact on referral compliance was not demonstrated. Limited evidence was found for the effectiveness of health education alone to boost screening attendance for either subgroup.DiscussionThe evidence for effectiveness in reducing inequities is not always direct, uses mixed outcomes, and had heterogenous designs. Yet, the results of the higher quality publications in this review indicate modest improvements worth pursuing further.Systematic Review Registrationhttps://osf.io/yr7tg/files/osfstorage?view_only=968ba9e8c910470ca227dcdb0da3cda8.